What are the enablers of and barriers to the creation of Organisations with an enhanced learning capacity? A systematic Review of learning organisation interventions - Laenen, Inneke (Department of Public Health and Family Medicine, 2020)
Health systems, like commercial enterprises, face wide-ranging challenges and need to develop an adaptive capacity in order to remain effective. There is increasing recognition in the health sector that the concept of the learning organisation, which has long been popular in the business management field, could be a key strategy to develop this adaptive capacity in health systems. Although examples exist of the application of learning organisation principles to health care facilities, there is little guidance for how units or groups responsible for health policy and strategies can apply them more widely. In order to provide some initial guidance to the Western Cape Department of Health, which has expressed an interest in developing into a learning organisation, this project sought to identify the enablers of, and barriers to learning organisation creation by conducting a systematic review of learning organisation interventions across multiple sectors. As multiple definitions and models of a learning organisation exist in the literature, this systematic review was complemented by an initial review of conceptual literature which synthesised the existing definitions and models of a learning organisation and identified a core set of learning organisation dimensions. Findings indicate that a foundation of good organisational software such as a shared understanding of, and commitment to a learning organisation vision, a culture which is conducive to learning organisation creation, and a secure, supportive and interpersonally non-threatening environment, is essential for learning organisation creation. Building on this foundation it is then important to invest in staff time (i.e. that staff are officially allowed, and incentivised, to spend time on learning during work hours), and the infrastructure and processes necessary to support knowledge transfer, such as physical meeting spaces, online learning databases, mentorship programmes, and feedback mechanisms.